Eosinophils mediate the pathogenesis of halothane‐induced liver injury in mice12. Issue 5 (15th March 2013) - Proctor, William R.; Chakraborty, Mala; Chea, Lynette S.; Morrison, Jeffrey C.; Berkson, Julia D.; Semple, Kenrick; Bourdi, Mohammed; Pohl, Lance R.
Abstract: Drug‐induced liver injury (DILI) is a major health issue, as it remains difficult to predict which new drugs will cause injury and who will be susceptible to this disease. This is due in part to the lack of animal models and knowledge of susceptibility factors that predispose individuals to DILI. In this regard, liver eosinophilia has often been associated with DILI, although its role remains unclear. We decided to investigate this problem in a murine model of halothane‐induced liver injury (HILI). When female Balb/cJ mice were administered halothane, eosinophils were detected by flow cytometry in the liver within 12 hours and increased thereafter proportionally to liver damage. Chemokines, eotaxin‐1 (CCL11) and eotaxin‐2 (CCL24), which are known to attract eosinophils, increased in response to halothane treatment. The severity of HILI was decreased significantly when the study was repeated in wildtype mice made deficient in eosinophils with a depleting antibody and in eosinophil lineage‐ablated ΔdblGata −/− mice. Moreover, depletion of neutrophils by pretreating animals with Gr‐1 antibody prior to halothane administration failed to reduce the severity of HILI at antibody concentrations that did not affect hepatic eosinophils. Immunohistochemical staining for the granule protein, major basic protein, revealed that eosinophils accumulated exclusively around areas of hepatocellular necrosis. Conclusion : Our findings indicate that eosinophils have a pathologic role in HILI in mice and suggest that they may contribute similarly in many clinical cases of DILI. (HEPATOLOGY 2013)